Export and innovation activities in the German service sector: empirical evidence at the firm level - Günther Ebling; Norbert Janz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
In this paper we analyse the relationship between export and innovation activities of German service sector companies using data from the 1997 wave of the Mannheim Innovation Panel in the Service Sector. There is a lot of support for the Schumpeterian hypothesis of export activities being mainly driven by innovation activities. Factor endowment theories are only partially supported. While human capital significantly improves export performance, labour costs hamper it only in selected branches. Moreover, allowing for simultaneity we find that export activities do not enforce innovation activities.
Keywords: L80; C53; O31; F14; 330; exports; innovation; service sector; firm behaviour; applied microeconometrics; Dienstleistungssektor; Internationaler Dienstleistungsverkehr; Export; Innovation; Schätzung; Deutschland